Incidence and predictors of virological failure among children receiving first-line anti-retroviral treatment in public comprehensive specialized hospitals found in Northeast Ethiopia: a retrospective follow-up study - Abebe, Estifanos Belay; Gebregeorgis, Meseret Ekubay; Seid, Fuad Ahmed; Zemariam, Alemu Birara; Dejene, Tadesse Mamo; Masresha, Seteamlak Adane (Frontiers in Pediatrics, 2024)
Despite Anti-Retroviral Treatment coverage in resource-limited countries is highly appreciated, the occurrence of first-line virological failure is the priority agenda. Therefore, this study aimed to assess Incidence and Predictors of Virological Failure among Children Receiving First Line Anti-Retroviral Treatment in Public Comprehensive Specialized Hospitals Found in North East Ethiopia. A multicenter institution-based retrospective follow-up study was conducted on the medical records of 481 HIV-infected children who were on first-line antiretroviral therapy from January 1, 2017 to December 31, 2021. Data were retrieved from May 15 to June 15, 2022 at three public comprehensive specialized hospitals. A simple random sampling technique was used to recruit study participants. STATA-14 was used to analyze the data, which was entered using EpiData version 4.6.2.0. The Kaplan-Meier estimator was used to estimate the survival. Both bi-variable and multivariable Cox regression models were fitted to identify predictors. Finally, an AHR with a 95%CI was computed, and variables with a p-value of < 0.05 were considered statistically significant predictors of virological failure. A total of 481 children records were included in the final analysis and observed for a 16,379 person-months follow-up period. From these, 60(12.47%) had developed virological failure, and the overall incidence density rate of 3.67(95% CI; 2.84, 4.73) per 1000 person-month observations. The hazards of VF among children were increased by recent WHO stage III&IV (AHR= 3.688; 95%CI: 1.449-6.388), poor ART adherence (AHR= 3.506; 95%CI: 1.711-7.234), and living in a rural environment (AHR = 5.013; 95%CI: 1.958- 8.351). Conversely, while the age of caregivers was less than 40 years the hazards were reduced by 60% (AHR=0.405; 0.003-0.449). : The incidence rate of virological failure was relatively high. Living in a rural area, adhering to ART poorly, being in a recent advanced WHO clinical stage, and having a caregiver of 40 years of age or older were all independent predictors of virological failure in children. Patients or parents (caregivers) need to be aware of the importance of strictly adhering to treatment regimens to prevent virological failure.